AGRICULTURAL FINANCING AND AGRICULTURAL OUTPUT IN NIGERIA: EVIDENCE FROM VECM APPROACH - MUHAMMAD, AUWAL ABUBAKAR; ISAH, HARIR ADAMU (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study analyzes the effect of agricultural financing on agricultural output in Nigeria between 1990 and 2021. Using a Vector Error Correction Model (VECM), it evaluates the roles of commercial banks, microfinance banks, and the Agricultural Credit Guarantee Scheme Fund (ACGSF). Secondary time series data sourced from the Central Bank of Nigeria underwent unit root and cointegration testing in E-Views 10. The results confirm a long-run equilibrium relationship between agricultural financing and output. Specifically, microfinance credit and ACGSF disbursements significantly and positively influence agricultural output. In contrast, credit from commercial banks has a negative long-run impact. Short-run dynamics show limited responsiveness, with the error correction term indicating slow adjustment toward equilibrium. The study recommends strengthening microfinance institutions, reforming the ACGSF to ease collateral constraints, and restructuring commercial bank credit to address risk aversion and high interest rates.